The Relationship "Parents and Child" In Russian and German - Siddikova Nargiza Badirovna (International Journal on Human-Computing Studies, 2023)
In line with comparative linguistics (based on the proverbial fund of the Russian and German languages), “parents – children” is described. Features indicated representations of the relationship between parents and children in both linguistic cultures, similarities and differences due to mentality and cultural identity are identified representatives of the described language communities.